2020
DOI: 10.1007/s00431-020-03785-3
|View full text |Cite|
|
Sign up to set email alerts
|

Vascular diameter and intima-media thickness to diameter ratio values of the carotid artery in 642 healthy children

Abstract: In children, arterial alterations occur with increased intima-media thickness as well as vascular diameter enlargement. Both conditions correlate with higher cardiovascular risk in adults, and both the array and proportion of these alterations are important hemodynamic parameters. In terms of functional adaptation processes, they influence several arterial wall properties as for example the shear and tensile stress of the vessel. There are no reference values for the vascular diameter and intima-media thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…We have shown that CCAd increases with maturation and in a sex dependent manner, with larger CCAd in boys compared to girls. These findings are similar to previous work noting increases in CCAd with age (28,29), and larger diameters in boys up to 14-15 years of age (29). The relationship between chronological age, global and regional CBF has been assessed using perfusion MRI in a large cross-sectional cohort of 1098 children (30).…”
Section: Age Maturation and Cerebrovascular Developmentsupporting
confidence: 87%
See 1 more Smart Citation
“…We have shown that CCAd increases with maturation and in a sex dependent manner, with larger CCAd in boys compared to girls. These findings are similar to previous work noting increases in CCAd with age (28,29), and larger diameters in boys up to 14-15 years of age (29). The relationship between chronological age, global and regional CBF has been assessed using perfusion MRI in a large cross-sectional cohort of 1098 children (30).…”
Section: Age Maturation and Cerebrovascular Developmentsupporting
confidence: 87%
“…Developmental data on the cervical arteries in healthy children and adolescents are also sparse. Increases in CCA diameter have been shown with age (28,29), and there is evidence of larger CCA diameters in boys compared to girls (29). A substantial increase in the ICA diameter with age has been reported in children, with larger ICA diameter in 10-19 year old youth compared to 4-9 year old children (33).…”
Section: Age Maturation and Cerebrovascular Developmentmentioning
confidence: 97%
“…All parameters were calculated as the average of four measurements. SDS were calculated using German reference values, which were assessed with the same protocol and equipment (ProSound Alpha 7 with a linear array of 5-13 MHz, Hitachi Healthcare, Tokyo, Japan) (Weberruß et al, 2015;Semmler et al, 2020).…”
Section: Carotid Structure and Functionmentioning
confidence: 99%
“…All the scaffolds in the present study withstood large elongation, and their stiffness levels did not change significantly (p > 0.05) with the addition of ECM proteins to PU (Table S1 ). Although the addition of ECM proteins reduced the tensile strength of the scaffolds significantly (p < 0.05), this may not be a problem as tensile strengths as low as 100 kPa have been reported previously for blood vessels 45 . Nevertheless, as tensile strength is directly proportional to burst pressure 44 , methods to improve the mechanical properties of such scaffolds should be investigated.…”
Section: Discussionmentioning
confidence: 48%